Field Simulation for Interstitial Microwave Hyperthermia Using a Finite Integration Algorithm - Erb, J.; Engelbrecht, Rainer; Schaller, Gerd; Müller, R. G.; Sauer, R. (26. Wissenschaftliche Tagung der Deutschen Gesellschaft für Medizinische Physik (DGMP) - Röntgen Centenary Congress, 1995)
UnivIS-Import:2015-04-16:Pub.1995.tech.IE.LEH.fields_8

Isolated meningomyeloradiculitis following infection with tick borne encephalitis virus - Racz, Attila; Schaller, Gerd; Lunkenheimer, Jens; Engelhorn, Tobias; Dörfler, Arnd; Sperling, Wolfgang; Schwab, Stefan; Maihöfner, Christian (Clinical Neurology and Neurosurgery, 2012)
CRIS-Team Scopus Importer:2022-08-05
Keywords: Meningomyeloradiculitis; Myelitis; Polyradiculitis; Tick borne encephalitis virus

Neutral Sphingomyelinase is an Affective Valence-Dependent Regulator of Learning and Memory - Kalinichenko, Liubov; Abdel-Hafiz, Laila; Wang, An Li; Mühle, Christiane; Rösel, Nadine; Schumacher, Fabian; Kleuser, Burkhard; Smaga, Irena; Frankowska, Malgorzata; Filip, Malgorzata; Schaller, Gerd; Richter-Schmidinger, Tanja; et al. (Cerebral Cortex, 2021)
Sphingolipids and enzymes of the sphingolipid rheostat determine synaptic appearance and signaling in the brain, but sphingolipid contribution to normal behavioral plasticity is little understood. Here we asked how the sphingolipid rheostat contributes to learning and memory of various dimensions. We investigated the role of these lipids in the mechanisms of two different types of memory, such as appetitively and aversively motivated memory, which are considered to be mediated by different neural mechanisms. We found an association between superior performance in short- A nd long-term appetitively motivated learning and regionally enhanced neutral sphingomyelinase (NSM) activity. An opposite interaction was observed in an aversively motivated task. A valence-dissociating role of NSM in learning was confirmed in mice with genetically reduced NSM activity. This role may be mediated by the NSM control of N-methyl-d-aspartate receptor subunit expression. In a translational approach, we confirmed a positive association of serum NSM activity with long-term appetitively motivated memory in nonhuman primates and in healthy humans. Altogether, these data suggest a new sphingolipid mechanism of de-novo learning and memory, which is based on NSM activity.
CRIS-Team Scopus Importer:2021-02-12
Keywords: ceramide; learning; memory; neutral sphingomyelinase; sphingomyelin

Serial repetitive transcranial magnetic stimulation (rTMS) decreases BDNF serum levels in healthy male volunteers - Schaller, Gerd; Sperling, Wolfgang; Richter-Schmidinger, Tanja; Mühle, Christiane; Heberlein, Annemarie; Maihöfner, Christian; Kornhuber, Johannes; Lenz, Bernd (Journal of Neural Transmission, 2014)
Although repetitive transcranial magnetic stimulation (rTMS) is established in the treatment of depression, there is little knowledge about the underlying molecular mechanisms. In the last decade, the neurotrophic hypothesis of depression entailed a plethora of studies on the role of neurogenesis-associated factors in affective disorders and rTMS treatment. In the present study, we hypothesised a sham-controlled increase of peripheral brain-derived neurotrophic factor (BDNF) levels following serial rTMS stimulations in healthy individuals. We investigated the influence of a cycle of nine daily high-frequency (HF)-rTMS (25 Hz) stimulations over the left dorsolateral prefrontal cortex (DLPFC) on serum levels of BDNF in 44 young healthy male volunteers. BDNF serum concentrations were measured at baseline, on day 5 and on day 10. Overall, the statistical analyses showed that the active and sham group differed significantly regarding their responses of BDNF serum levels. Contrary to our expectations, there was a significant decrease of BDNF only during active treatment. Following the treatment period, significantly lower BDNF serum levels were quantified in the active group on day 10, when compared to the sham group. The participants' smoking status affected this effect. Our results suggest that serial HF-rTMS stimulations over the left DLPFC decrease serum BDNF levels in healthy male volunteers. This provides further evidence for an involvement of BDNF in clinical rTMS effects.
EVALuna2:23619